Параметричне дослідження звукозахисних властивостей нового типу бар’єрів - Леськів, Ігор; Дівеєв, Богдан (Видавництво Львівської політехніки, 2011)
У густонаселеному місті з багатоповерховими будівлями, шумове забруднення - один з екологічних факторів, що мають високий пріоритет. Житлові будинки, лікарні і інші шумочутливі будівлі розміщені поблизу від великих шосе. Від збільшення об'єму рухушум транспортування збільшується і це серйозно впливає на якість та тривалість життя більшості громадян, що живуть в цих густонаселених районах. Серед різний заходи для шумового послаблення в багатоповерховихмістах, придорожнішумові бар'єри - один з найекстенсивніше використовуваних методів для шумопониження. Щоб оцінити ефективність шумових бар'єрів потрібні точні характеристики екранування на проектній стадії. Sound wave propagation over obstacles such as noise barriers and buildings are of great importance in many practical applications. The simplest problem is single diffraction of sound by a screen or wedge, for which numerous works have been done and an excellent literature review can be found in the paper [1]. Modifications to the top edged of noise barriers have been shown to be capable of improving noise barrier attenuation over that of a plane barrier of the same height. Two simple devices that have been shown to offer significant gains in insertion loss are the absorbent T-top and multi-edge configurations [2, 5]. Although the former seems to have the greatest potential, its application in practice has been very limited because conventional acoustic absorption treatments using porous materials are not very durable in situations such as this. Nonconventional approaches have been proposed such as the use of quadratic residue diffusers instead of porous material and these offer significant performance gains [4]. Damped dynamic vibration absorbers (DVA’s) are used to provide energy dissipation, thereby motivating the term ‘absorber’. These realistic absorbers furthermore reduce their sensitivities to parameter variations from optimal values and reduce the primary system motion at its resonance frequencies, while increasing their effective bandwidth, as compared to undamped examples. Detailed descriptions of the fundamentals of such DVA’s are given in [5,6]. This study aims to predict the sound transmission properties of composite laminated thin-walled structures with the inclusions. In this paper, the effective stiffness constants of equivalent to sandwich type laminates Timoshenko beam and their damping properties have been determined by using a procedure based on multilevel numerical schemes and eigen frequencies [7,8]. Numerical evaluations obtained for the vibration of the equivalent Timoshenko beam have been used to determine the sound transmission properties and low frequency noise control of laminated composite beams with inclusions. This paper deals with the parametric investigation of noise impact on innovative barriers: layered plates with the DVA’s system.
A parametric investigation of noise protection properties of innovative barriers
Keywords: шум; бар’єри; характеристики екранування; обертові машини оптимальне проектування